FACTOR-FACTOR THAT INFLUENCING INDEPENDENCE OF PUBLIC-SECTOR AUDITOR: A LITERATURE REVIEW - Doan Anh Vu (Universitas Agung Podomoro, 2023)
The study of public sector audit is a relatively large, complex, unexplored and under-recognized field. Therefore, researchers call for more studies on public sector audit, especially in the context of developing countries. This article gives review of academic study pertaining to public-sector auditors’ independence and factors affecting public-sector auditors’ independence. This literature review is implemented based on published papers in 20th century in prestigious journals related to public sector audit. Firstly, we review and explain definition of independence clearly. Secondly, we organize our review around three main threats to public-sector auditors’ independence, namely, (a) political manifestos, (b) auditor tenure, and (c) relationship with auditee. For each of the threats, this study discusses the effects of each threat on the public-sector auditors’ independence. Additionally, we conclude that proofs together with recent changes, provides for future study on public-sector auditor’s independence.